Transparency and stock price volatility: european evidence - Vieira, Elisabete F. Simões (2012)
This paper studies the key determinants of the information transparency and its consequences for the market, namely in what concerns the stock price volatility, analysing the disclosure practices of two European countries. A transparency and a volatility model are applied. Based on annual reports information, we could not find any significant relationship between transparency and volatility. However, considering the quarterly reports, we find a negative relation between these variables for the second quarter, suggesting that the higher the transparency, the lower the stock price volatility. This research contributes to the recent literature on the information transparency and stock price volatility, analysing two small European countries that are clearly in need of research.